2023
DOI: 10.3389/feduc.2023.1197938
|View full text |Cite
|
Sign up to set email alerts
|

Supporting pre-service teachers in developing research competence

Abstract: IntroductionTeachers need research competence to reflect on their teaching and to interpret and implement research-based recommendations. However, many pre-service teachers have critical attitudes toward research, little motivation to engage in research, and comparatively low knowledge of research methods and thereby consequently indicating a low research competence. Flexible online modules in university teaching could be a promising approach to address these issues. Online modules can potentially promote self… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
1
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(3 citation statements)
references
References 45 publications
0
1
0
Order By: Relevance
“…This finding of a positive relationship of engagement and motivation with employment status is consistent with some studies (Ogbonnaya et al, 2020;Malabanan et al, 2022) but inconsistent with others. For example, Gussen et al (2023) concluded that many pre-service teachers have negative attitudes toward research and lack the motivation to conduct it, while Ye et al (2021) found that pre-service teachers demonstrated better motivation than beginners, except for a few factors like intrinsic value and teaching skills. These discrepancies imply that motivation levels may vary over a teacher's tenure.…”
Section: Research Questionmentioning
confidence: 99%
“…This finding of a positive relationship of engagement and motivation with employment status is consistent with some studies (Ogbonnaya et al, 2020;Malabanan et al, 2022) but inconsistent with others. For example, Gussen et al (2023) concluded that many pre-service teachers have negative attitudes toward research and lack the motivation to conduct it, while Ye et al (2021) found that pre-service teachers demonstrated better motivation than beginners, except for a few factors like intrinsic value and teaching skills. These discrepancies imply that motivation levels may vary over a teacher's tenure.…”
Section: Research Questionmentioning
confidence: 99%
“…When we consider ICT's role in instructional design, communication competence becomes even more critical. Effective communication is a prerequisite to effectively conveying pedagogical concepts, whether through direct instruction or through the use of ICT tools (Gussen et al, 2023;Kinskey, 2017). Pre-service teachers with high competence in communication can better understand and apply these concepts to instructional design using ICT tools, leading to improved learning experiences for their students.…”
Section: Competence For Communication Skills (Comp)mentioning
confidence: 99%
“…The enhancement of communication abilities in pre-service educators is a complex and multifaceted undertaking. The significance of cultivating research competence, which encompasses critical thinking, ethical reasoning, and proficient communication of research findings, is underscored in a study (Gussen et al, 2023). This underscores the necessity for pre-service educators to possess the ability to articulate intricate concepts with clarity and efficacy.…”
Section: Introductionmentioning
confidence: 99%